Characterization of inhibitory activity of camel urine on human platelet function. Issue 1 (February 2016) - Alyahya, Asma M.; Abdel Gader, Abdel Galil M.; Alhaider, Abdulqader A.
الملخص: الأهداف: أظهرت دراسات سابقة أن كلا من بلازما الإبل وأبوالها تحمل خاصية مثبطة لوظائف الصفائح الدموية البشرية. لذا هدفت هذه الدراسة لمعرفة ما إذا كان وجود العنصر المثبط لوظائف الصفائح الدموية البشرية، تتم تصفيته من بلازما الإبل إلى أبوالها أو يتم إفرازه من الكلى، ودراسة ما إذا كانت ظروف الإبل الإنجابية لها أي تأثير على هذا النشاط المثبط. طرق البحث: شملت الدراسة ٦٧ من إناث الإبل (حواملا وأبكارا ومرضعات) واستُعمل اختبار وظائف الصفائح الدموية بقياس أثر التكدس على نقل الضوء، وباستعمال جهاز تحليل وظائف الصفائح الدموية. النتائج: أظهرت النتائج انخفاضا كبيرا في استجابة تراكم الصفائح الدموية للإبل للمواد المحفزة بالمقارنة بالصفائح الدموية البشرية. وعلاوة على ذلك أحدثت إضافة أبوال الإبل تثبيطا كبيرا لاستجابة تراكم الصفائح الدموية البشرية للتحفيز. ولقد وُجد عند بعض الإبل خاصية تثبيط تراكم الصفائح الدموية البشرية عند إضافة البلازما والبول، بينما في البعض الآخر وُجد لديهم خاصية تثبيط تراكم الصفائح الدموية البشرية إما في البلازما أو البول. وُجد أن أبوال الإبل التي لديها تثبيطا كبيرا للصفائح الدموية، تحدث تثبيطا كبيرا لصفائح الدم البشرية أيضا. وقد تأكد هذا التثبيط من خلال جهاز تحليل وظائف الصفائح الدموية. هذا وقد أظهرت الإبل المرضعة نشاطا مثبطا أقوى لأبوالها مقارنة بالفئات الأخرى من الإبل. الاستنتاجات: تشير النتائج إلى أن عامل تثبيط الصفائح الدموية البشرية الذي ثبت وجوده في أبوال الإبل يصل إلى الأبوال من خلال تصفيته من بلازما الدم. لكن لا يمكن استبعاد الكلى كمصدر منتج لها. كما يبدو أن الإبل المرضعة تمتلك نشاطا مثبطا أقوى لأبوالها مقارنة بغيرها من الإبل. هذه النتائج تدعم حقيقة المقولات المعروفة للخصائص العلاجية المفيدة لأبوال الإبل التي قد تنشأ جزئيا في الكلى، كما يمكن أن تتم تصفيتها من البلازما. Abstract: Objectives: Previous studies have shown that both camel plasma and urine display inhibitory action on human platelet function. This study aimed to determine whether the platelet-inhibiting activity in camel plasma is filtered into urine or if this activity is initiated by the kidney and to evaluate the impact of the camel's reproductive status on this inhibitory activity. Methods: The study included 67 non-pregnant, pregnant and lactating female camels. Platelet function was tested in the camels by light transmission aggregometry and platelet function analyser (PFA-100 ® ) studies. Results: In comparison to the results in human beings, camel platelet aggregation responses to both adenosine diphosphate (ADP) and arachidonic acid (AA) agonists showed a significant reduction. Furthermore, human platelet aggregation responses were significantly inhibited by camel urine. Some camels displayed inhibitory activity in both plasma and urine, while others displayed this activity in either blood or urine. In camel categories with markedly inhibited platelet aggregation responses, urine caused marked inhibition of human platelets. In camels with antiplatelet urine effects, camel platelet inhibition was also confirmed by prolongation of platelet function analyser 100 (PFA-100 ®) closure times in all categories. Lactating camels showed stronger urine inhibitory activity compared to other groups. Conclusions: These findings suggest that an inhibitory factor could be filtered from camel plasma; however, a renal source cannot be excluded. Lactating camels seem to possess more potent urine inhibitory activity compared to other camel groups. These findings support the fact that the claimed beneficial therapeutic properties of camel urine originate in part from the kidney and could be filtered from plasma.